The crosstalk among the physical tumor microenvironment and the effects of glucose deprivation on tumors in the past decade - Cui, Yingnan; Sun, Yuanlin; Li, Dongming; Zhang, Yuzheng; Zhang, Yangyu; Cao, Donghui; Cao, Xueyuan (Frontiers in Cell and Developmental Biology, 2023)
The occurrence and progression of tumors are inseparable from glucose metabolism. With the development of tumors, the volume increases gradually and the nutritional supply of tumors cannot be fully guaranteed. The tumor microenvironment changes and glucose deficiency becomes the common stress environment of tumors. Here, we discuss the mutual influences between glucose deprivation and other features of the tumor microenvironment, such as hypoxia, immune escape, low pH, and oxidative stress. In the face of a series of stress responses brought by glucose deficiency, different types of tumors have different coping mechanisms. We summarize the tumor studies on glucose deficiency in the last decade and review the genes and pathways that determine the fate of tumors under harsh conditions. It turns out that most of these genes help tumor cells survive in glucose-deprivation conditions. The development of related inhibitors may bring new opportunities for the treatment of tumors.